KUALITAS PELAYANAN PADA PEUSAHAAN UMUM DAERAH TIRTA MON KRUENG BARO KABUPATEN PIDIE - Awaluddin Awaluddin; Zulfikar Zulfikar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Public service is public trust, where every citizen hopes that public services can provide services that are in accordance with honesty, and management of income sources that are appropriate, accountable, and generate public trust, which requires public service ethics as a pillar, public trust. and as a basis for realizing good governance, the quality of public services is a dynamic condition related to services, people, products, processes and the environment where the level of quality is determined at the time the service is provided. As for the formulation of the problem, how is the quality of clean water supply services at the Tirta Mon Krueng Baro Regional Public Company, Pidie Regency? and the methodology used using a descriptive qualitative approach is limited to efforts to reveal a problem or situation or event as it is so as to reveal facts and provide an objective picture of the actual state of the object under study. Based on the results of this study, it can be said that at PDAM Tirta Mon Krung Baro, Pidie Regency, the quality of service provided to customers. Honesty is part of spirituality that reflects the attitude of sharing, which is in favor of truth and a commendable moral attitude, and honesty is a personal quality possessed by every individual in the company. Services at PDAM Tirta Mon Krung Baro, Pidie Regency, not only show the existence and ability of employees to serve, but employees also deeply instill in themselves the responsibility as public servants. Structurally it is carried out by the Subscription Section, considering that the entire service administration process occurs in this section.Keywords: Quality, Service, Company